Ted's shed - Cox, Phil Roxbee; Cartwright, Stephen; Tyler, Jenny (Tulsa, Okla. : EDC, 2001)
Ted moves his red bed into his shed and then changes the shed into a caravan.
"A phonics reader"--Cover.
Lift-the-flap pages.
2.3.
2.3
K-3
Keywords: Toy and movable books -- Specimens; Teddy bears -- Fiction; Toy and movable books; Teddy bears -- Fiction; Toy and movable books